Assessment of factors contributing to flood disaster in Ibadan metropolis: implication for environmental health education (2015)
Climate change has brought with it some forms of extreme weather events One of such is heavy rainfall which often leads to flood In recent times, flood disaster has been a regular occurrence destroying lives and property This study was earned out to identify and assess contributing factors to flood disaster in Ibadan metropolis The study investigated the contributions of variables such as heavy rainfall, drainage system, waste disposal arrangement, the dumping of refuse inside waterways the role of environmental health officers and level of adherence to the city masterplan. Expost facto research design was adopted for the study The population composed all residents of Ibadan metropolis The sample consisted of seven hundred and fifty (750) respondents were sampled from flood affected areas in five Local Government Areas of Oyo State, Nigeria. The instrument used was self-constructed questionnaire with 0.78 reliability co-efficient. The data obtained were analyzed using frequency counts, percentages and inferential statistics of regression The findings revealed that dumping of refuse inside waterways, attitude of environmental health officers, heavy rainfall drainage system and poor adherence to city master-plan contributed io flood disaster in Ibadan metropolis. Among the factors that contributed significantly are heavy rain and dumping of refuse inside waterways. It is implied from the findings that there is urgent need for environmental health education for the population in order to encourage proper disposal of waste among residents of Ibadan metropolis.